2016
DOI: 10.1159/000447825
|View full text |Cite
|
Sign up to set email alerts
|

Impact of miR-208 and its Target Gene Nemo-Like Kinase on the Protective Effect of Ginsenoside Rb1 in Hypoxia/Ischemia Injuried Cardiomyocytes

Abstract: Background/Aims: Ginsenoside Rb1 (GS-Rb1) is one of the most important active pharmacological extracts of the Traditional Chinese Medicine ginseng, with extensive evidence of its cardioprotective properties. Mir-208 has been shown to act as a biomarker of acute myocardial infarction in vivo studies including man. However the impact of miR-208 on the protective effect of GS-Rb1 in hypoxia/ischemia injured cardiomyocytes remains unclear. The current study aims to investigate the target gene of miR-208 and the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Although it is unlikely that a single biomarker of myocardial ischemic injury will be sufficient to manage AMI diagnosis, a combination of different biomarkers, including circulating miRNAs, may enhance diagnostic sensitivity and specificity [28]. Numerous circulating miRNAs, including miR-208a, miR-126, miR-223-3p, miR-150, miR-19b-3p, miR-21, miR-328, and miR-134, showed potential as biomarkers for cardiovascular diseases [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is unlikely that a single biomarker of myocardial ischemic injury will be sufficient to manage AMI diagnosis, a combination of different biomarkers, including circulating miRNAs, may enhance diagnostic sensitivity and specificity [28]. Numerous circulating miRNAs, including miR-208a, miR-126, miR-223-3p, miR-150, miR-19b-3p, miR-21, miR-328, and miR-134, showed potential as biomarkers for cardiovascular diseases [28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, miR-3546 was selected to further determine its effect on sublytic C5b-9-triggered GMC apoptosis and the related regulatory mechanism. Notably, miR-3546 belongs to miR-208 family, and though several documents have pointed out that miR-208 has regulatory role in myocardial injury [42][43][44], there has not been any report about the function of miR-3546.…”
Section: Discussionmentioning
confidence: 99%
“…Culture of neonatal rat cardiomyocytes (NRCMs) from heart tissues. Primary cultures of NRCMs from a total of 180 12-24 h-old male Sprague Dawley rats (weight range, 5-6 g; Laboratory Animal Center, Jilin University, Changchun, China) were prepared through gentle serial trypsinization, as described previously (12)(13)(14). All animal protocols were approved by the Animal Care Center and Use Committee of Jilin University (Changchun, China).…”
Section: Methodsmentioning
confidence: 99%
“…Ginsenoside Rb1 (GS-Rb1) is the most active and abundant monomer in ginseng (11). Although a number of studies have demonstrated the protective effects of GS-Rb1 on the heart (11)(12)(13)(14) and recent studies have revealed that GS-Rb1 could impact miR expression in hypoxia/ischemia-injured cardiomyocytes (12,13), the miR targets involved and their roles in the heart remain unknown. Therefore, in the current study, the roles and mechanisms of miR-21 and its target gene, which encodes PDCD4, in the protection of cardiomyocytes treated with GS-Rb1 were studied by constructing an oxygen-glucose deprivation (OGD) injury model in vitro.…”
Section: Introductionmentioning
confidence: 99%